2000
DOI: 10.1111/j.1745-4565.2000.tb00302.x
|View full text |Cite
|
Sign up to set email alerts
|

BACTERICIDAL EFFICIENCIES OF COMMERCIAL DISINFECTANTS AGAINST LISTERIA MONOCYTOGENES ON SURFACES

Abstract: The efficiencies of potassium persulphate, isopropanol, hydrogen peroxide and peracetic acid, quaternary ammonium compound, hypochlorite, sodium dichloroisocyanurate, ethanol and phenol derivatives, tertiary alkylamines and dimethyl alamine betaine‐based disinfectants and a hypochlorite‐based disinfecting cleaning agent were evaluated against eight Listeria monocytogenes strains representing three different ribotypes. All the disinfectants were effective in a suspension test with an exposure time of 30 s at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 22 publications
4
44
0
4
Order By: Relevance
“…At a very low concentration, the organisms were able to survive in the biocides. This was also observed in the study by Kaarina et al (24).…”
Section: Salmonella Sppsupporting
confidence: 79%
“…At a very low concentration, the organisms were able to survive in the biocides. This was also observed in the study by Kaarina et al (24).…”
Section: Salmonella Sppsupporting
confidence: 79%
“…In order to maintain hygienic standards in the food industry, regular cleaning of equipment must be undertaken. However, it has been shown that the susceptibility of cells to biocides may be reduced by the presence of organic material on the surface (Aarnisalo et al, 2000;Bagge-Ravn et al, 2003;Gram et al, 2007). Retained organic material on a surface may also impede the recovery of cells and methods of detection (Whitehead et al, 2009a).…”
Section: Introductionmentioning
confidence: 96%
“…Aarnisalo et al (2000) reported such a situation using 8 strains of L. monocytogenes and testing the effectiveness of 10 disinfectants typical for the food industry. Le Chevallier et al (1988), Wirtanen and Juvonen (2002) and other authors compared the basic tests with the surface tests and gave evidence of the primary importance of the surface tests.…”
Section: Effectiveness Of Biocides Against Biofilms In the Food Industrymentioning
confidence: 99%